COVID-19 and the future of work in the hospitality industry. (August 2021) - Huang, Arthur; De la Mora Velasco, Efren; Marsh, Jessica; Workman, Hannah
Abstract: The COVID-19 pandemic has significantly disrupted the hospitality industry. This research combines different data to examine the US labor market trends during COVID-19. It is found that low-preparation jobs in leisure and hospitality are the hardest hit and slow to recover. The pandemic has highlighted growing issues in workplace safety, skill gaps, technology adoption, and work reorganization in the hospitality industry. This paper develops two propositions about preparing hospitality workers for the future of work and providing flexible work arrangements. Highlights: Different data was combined to examine the US labor market trends during COVID-19. Low-preparation jobs in hospitality are the hardest hit and are slow to recover. Flexible work arrangements may support hospitality workers and businesses in adapting to changing labor markets. Public-private-academic partnerships could assist hospitality organizations in upskilling and reskilling workers.